The relationships between front crawl performance and hydrodynamics in young female swimmers. - Marinho, Daniel (2016)
The purpose of this study was to analyse the relationship between front crawl performance and hydrodynamic variables during leg kicking. Sixteen female age-group swimmers (9.2±0.6 years-old, 42.4±8.5 kg, 1.5±0.1 m) participated in this study. The 200m front crawl performance, the 200m front crawl kicking performance and the active drag during leg kicking were measured. The velocity perturbation method was used to determine active drag. The 200m front crawl performance was significantly correlated (p<0.01) with the performance in 200m kicking (0.89), the hydrodynamic drag force during leg kicking (-0.70), and with power output during kicking (-0.64). Drag coefficient values were not related to the performance in 200 m front crawl. These findings underline the importance of leg kicking to overall performance in front crawl swimming in these ages and can suggest the important role of kicking tasks during training in young swimmers.